Developmental origin of tendon diversity in Drosophila melanogaster - Moucaud, Blandine; Prince, Elodie; Jagla, Krzysztof; Soler, Cédric (Frontiers in Physiology, 2023)
Myogenesis is a developmental process that is largely conserved in both Drosophila and higher organisms. Consequently, the fruit fly is an excellent in vivo model for identifying the genes and mechanisms involved in muscle development. Moreover, there is growing evidence indicating that specific conserved genes and signaling pathways govern the formation of tissues that connect the muscles to the skeleton. In this review, we present an overview of the different stages of tendon development, from the specification of tendon progenitors to the assembly of a stable myotendinous junction across three different myogenic contexts in Drosophila: larval, flight and leg muscle development. We underline the different aspects of tendon cell specification and differentiation in embryo and during metamorphosis that result into tendon morphological and functional diversity.